Electron-beam irradiation of halogen free flame retardant polymers for wire and cable applications - Sabet, M. (Trans Tech Publications Ltd, 2014)
Effect of addition different polymers and fillers with electron beam irradiation on changes of physical, electrical and flammability properties of low density polyethylene (LDPE) / trimethylol propane trimethylacrylate (TMPTMA) / Irganox/ zinc borate (ZB) have been investigated. Results of measured gel content (GC), tensile strength (TS), elongation at break (EL), hot set (HS) tests, melt index (MFI), dielectric strength (DS), volume resistivity (VR), flammability and limiting oxygen index (LOI) have confirmed positive effects of adding maleic anhydride grafted LDPE (LDPEgMAH), ethylene vinyl acetate (EVA) and CS whereas effect of ATH to blends drastically had negative effects on improvement of physical properties of blends. Meanwhile, presence of TMPTMA and enhancing irradiation could improve properties seriously. Â© 2014 Trans Tech Publications, Switzerland.